2017
DOI: 10.3389/fpls.2017.00742
|View full text |Cite
|
Sign up to set email alerts
|

Boron Supply Enhances Aluminum Tolerance in Root Border Cells of Pea (Pisum sativum) by Interacting with Cell Wall Pectins

Abstract: Aluminum (Al) toxicity is the primary factor limiting crop growth in acidic soils. Boron (B) alleviates Al toxicity in plants, which is mainly considered to be due to the formation of Rhamnogalacturonan II-B (RGII-B) complexes, which helps to stabilize the cytoskeleton. It is unclear yet whether this is due to the increasing of net negative charges and/or further mechanisms. Kinetics of Al accumulation and adsorption were investigated using entire cells, cell wall and pectin of root border cells (RBCs) of pea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 62 publications
4
27
0
Order By: Relevance
“…2e), especially in WSP and ASP (Table S1), but was not statistically significant in Al content in HC1 and HC2, except for +Al B50 treatment (Fig. 2f-g), suggesting that B addition on the ability of pectin binding Al is more obvious than other components, and more specific action in ASP, which in line with the conclusion that ASP is the predominant target of Al accumulation in CW (Li et al , 2017). A large amount of pectin, HC1, and HC2 were observed under +Al B0.1 treatment (Fig.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…2e), especially in WSP and ASP (Table S1), but was not statistically significant in Al content in HC1 and HC2, except for +Al B50 treatment (Fig. 2f-g), suggesting that B addition on the ability of pectin binding Al is more obvious than other components, and more specific action in ASP, which in line with the conclusion that ASP is the predominant target of Al accumulation in CW (Li et al , 2017). A large amount of pectin, HC1, and HC2 were observed under +Al B0.1 treatment (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Similar conclusions were drawn in Arabidopsis research that the increase of Al binding in HC1 component inhibited root elongation (Zhu et al , 2012). Meanwhile, Al 3+ binding in pectin can also inhibit plant growth (Li et al 2017; Yan et al , 2018a), interestingly, different B levels supply decreased Al content in pectin gradiently (Fig. 2e), especially in WSP and ASP (Table S1), but was not statistically significant in Al content in HC1 and HC2, except for +Al B50 treatment (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Hematoxylin results in the present study confirmed that roots were heavily stained with dense blue color under + Al-B treatment due to Al-hematoxylin complex as shown in Figure 2(c). It has been documented that Bdeficiency increases the concentration of un-methylated pectin in the cell wall of roots, creating higher negative charges thus producing more favorable condition for Al binding (Stass et al 2007;Li et al 2017). Moreover, the role of B has been reported in the formation of the primary cell wall by cross-linking with pectic polypectic polysaccharide RG-II (rhamnogalacturonan II).…”
Section: Discussionmentioning
confidence: 99%